The Role of Teachers in Instilling Islamic Values in Young Children - Siti Nurhalimah Abbas; Mimit Pakasi; Junaedi Junaedi; Nurul Amaliah Hasbi; Yulmiati Latief (Jurnal Caksana : Pendidikan Anak Usia Dini, 2026)
Instilling Islamic values in early childhood is a crucial aspect of shaping children’s character and religious habits. However, research on the role of teachers in the process of internalizing values in Islamic early childhood education institutions remains limited. This study aims to analyze the role of teachers in the internalization of Islamic values through habit-forming practices at RA HS Muhdar Tapango. The study employs a qualitative, descriptive approach. The research participants consisted of one principal and two teachers selected through purposive sampling. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that teachers serve as educators, mentors, role models, motivators, and facilitators in the internalization of Islamic values. The internalization process is carried out through the habit formation of prayer, greetings, memorization of short surahs, religious practices, and the cultivation of Islamic ethics. This study offers a novel contribution in the form of conceptualizing the teacher’s role as a multidimensional actor within a habit-based value internalization model that integrates ritual and social dimensions. It is hoped that this study will serve as a reference for the development of values education in Islamic-based early childhood education institutions.